Crime and Circumstance: The Effects of Infant Health Shocks on Fathers’ Criminal Activity - Hope Corman
Few studies in the economics literature have linked individuals’ criminal behavior to changes in their personal circumstances. Life shocks, such as natural or personal disasters, could reduce or sever a person’s connections to his/her family, job, or community. With fewer connections, crime may become a more attractive option. This study addresses the question of whether an exogenous shock in life circumstances affects criminal activity. Specifically, we estimate the effects of the birth of a child with a random and serious health problem (versus the birth of a healthy infant) on the likelihood that the child’s father becomes or remains involved in illegal activities. Controlling for the father’s pre-birth criminal activity, we find that the shock of having a child with a serious health problem increases both the father’s post-birth conviction and incarceration by 1 to 8 percentage points, depending on the measure of infant health used.